Regulatory T-cell and T-helper 17 balance in chronic lymphocytic leukemia progression and autoimmune cytopenias. Issue 8 (3rd August 2015) - Lad, Deepesh P.; Varma, Subhash; Varma, Neelam; Sachdeva, Man Updesh Singh; Bose, Parveen; Malhotra, Pankaj
Abstract : The reasons for progression and autoimmune cytopenias (AIC) in chronic lymphocytic leukemia (CLL) are not entirely clear, with previous studies suggesting a role for regulatory T-cells (Treg). In this study we prospectively studied Treg (CD3 + CD4+ CD25highCD127low), interleukin-10 (IL-10) producing Treg and T-helper 17 (Th17) (CD3 + CD4+ IL-17+) cells in 40 treatment-naive patients with CLL. The percentage of Th17 and not Treg cells was significantly higher in the AIC cohort than in those without AIC ( p < 0.0001). The Treg:Th17 ratio was skewed in favor of Th17 in the AIC cohort ( p = 0.02). Th17 cells are responsible for AIC of CLL. Analysis of lymph-node aspirates showed that the percentage of Treg and IL-10 expression in Treg and not Th17 was significantly higher than in peripheral blood ( p < 0.01). Treg cells play a major role in the microenvironment where disease progression occurs. This shows the importance of maintaining the Treg:Th17 equilibrium, for imbalance leads to CLL progression or AIC.